Kajian Teknis Penjadwalan Pemeliharaan Kolam Pengendapan (Tailing Pond) PT. Bumi Khatulistiwa Bauksit Site Meliau Kabupaten Sanggau Kalimantan Barat - Kevin, Stephanus; Murad, Murad; Nirmala, Azwa (Universitas Tanjungpura, 2026)
PT. Bumi Khatulistiwa Bauksit (PT. BKB), a bauxite mining company, faces challenges in maintaining its tailing ponds. The lack of a structured maintenance schedule has led to sediment accumulation, which risks pond shallowing and environmental contamination from potential overflow. This study aims to evaluate the condition of the settling ponds and establish an optimal maintenance schedule. A quantitative approach was employed, combining primary field data with secondary data. Analytical steps included calculating design rainfall, rainfall intensity, total discharge, solid percentage, settling velocity, and maintenance/dredging time based on pond volume and sediment accumulation. Results indicate the highest daily total discharge in Pond 1 (17,276.23 m³/day) and the lowest in Pond 5 (5,022.97 m³ /day). Maintenance intervals vary: Pond 1 requires dredging every 1 month and 7 days; Pond 2, every 1 month and 22 days; Pond 3, every 1 year and 5 months and 12 days; Pond 4, every 4 months and 18 days; and Pond 5, every 6 years and 5 months and 12 days. The excavator’s productivity reaches 447.93 m³/hour, with dredging time per pond ranging from 8 to 35 days.